PEMANFAATAN BENTONIT TERPILAR ALUMINIUM - Abdish Shomad Nasrullah, ; Nurul Hidajati, (Matematika dan Sains, 2011)
This research is purposed to know adsorption capability of pillaring bentonite in regenerating the waste cooking oil. Pillaritation was carried out using aluminium, while the quality of waste cooking oil yielded from regeneration was observed based on the colour, acid number, water conten, and peroxide number. The results of research showed that the bentonite pillared by AlCl3.6H2O 0.3 M and NaOH 0.5 M gave the maximal characteristics, namely acid number (0.2549%), peroxide number (5.626413 meq), water content (776 ppm) and color brightness (L3.5). It can be concluded that the pillaring bentonite could improve the quality of waste cooking oil and suitable with the quality requirements of SNI 01-3741-2002. 3.6H2O 0.3 M and NaOH 0.5 M gave the maximal characteristics, namely acid number (0.2549%), peroxide number (5.626413 meq), water content (776 ppm) and color brightness (L3.5). It can be concluded that the pillaring bentonite could improve the quality of waste cooking oil and suitable with the quality requirements of SNI 01-3741-2002.